PRICE RISK MANAGEMENT IN THE WHEAT MARKET USING OPTION STRATEGIES - Bobriková, Martina (Economics of Agriculture, 2021)
Recently, the agricultural business is displayed a greater amount of risk because of price volatility growth. Consequently, it is necessary to have knowledge of how to regulate the risk of price fluctuations. This paper is concerned with the hedging techniques in the commodity market by the help of vanilla options. The main idea is to analyze option strategies with the ambition to demonstrate their utilization by hedging against increasing prices. Hedged buying price formulas are derived for every spot futures price. An additional contribution is considered for applying in the wheat trading. Chicago Mercantile Exchange products, i.e. wheat options on futures are investigated. The profitability of hedged scenarios is examined. A comparative analysis of the designed hedging variants is presented. Suggestions for potential wheat buyers are proposed.